SYNTHESIS OF SOME NEW 4-OXO-AZETIDINE DERIVATIVES FROM SCHIFF BASE DERIVATIVES CONTAINING PYRIDINE MOIETY AS ANTIMICROBIAL AGENTS - N. MADHAVI; B. LOURDU RANI (International Journal of Pharma and Bio Sciences, 2013)
A new series of 4-oxo-azetidine (4a-0) from Schiff base derivatives containing pyridine moiety are synthesized. The Schiff’s base on treatment with various aromatic aldehydes in ethanol in presence of a few drops of glacial acetic acid to afford Schiff base derivatives (3a-o).The Schiff base derivatives on treatment with dioxane and triethylamine afforded targeted compounds (4a-0).The structure of all synthesized compounds has been established on the basis of their spectral (IR, H1&C13 NMR and Mass) and analytical data. The purity of the compounds was confirmed by TLC. All the synthesized compounds were evaluated for their in vitro antimicrobial activity against fungi, Gram positive and Gram negative bacteria. Some of the compounds exhibited moderate activity when compared with reference standard Ciprofloxacin and Miconazole.